Short Communication: Some Observations on the Role of Bradykinin in Immunity to Teladorsagia circumcincta in Sheep - Andrew R. Williams (Journal of Parasitology Research)
Bradykinin is a physiologically active peptide involved in vasodilation and smooth muscle contraction and is previously shown to be increased in gastrointestinal mucus during nematode challenge in sheep. Here, it is shown that bradykinin in the abomasum is positively correlated with both mast cells and globule leukocytes in the abomasum, and that all three of these parameters are negatively associated with numbers of adult Teladorsagia circumcincta during the challenge of immune sheep. It is suggested that bradykinin either stimulates the degranulation of mast cells, or is released during this degranulation process, or both. Multiple regression showed that almost 60% of the variation of in adult T. circumcincta could be explained by two variables, bradykinin and T. circumcincta—specific IgG1 in plasma. This provides further evidence that bradykinin may be a mechanism of protective immunity in sheep, although its involvement in asthma and other allergic disorders raises questions about its role in unwanted immunopathology.